2019
DOI: 10.1152/japplphysiol.01098.2018
|View full text |Cite
|
Sign up to set email alerts
|

Daily heat treatment maintains mitochondrial function and attenuates atrophy in human skeletal muscle subjected to immobilization

Abstract: Skeletal muscle immobilization leads to atrophy, decreased metabolic health, and substantial losses in function. Animal models suggest that heat stress can provide protection against atrophy in skeletal muscle. This study investigated the effects of daily heat therapy on human skeletal muscle subjected to 10 days of immobilization. Muscle biopsies were collected, and MRIs were analyzed from the vastus lateralis of 23 healthy volunteers (11 women, 12 men) before and after either 10 days of immobilization with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 38 publications
6
68
3
2
Order By: Relevance
“…; Hafen et al . ). Much more research is needed to determine whether heat therapy would improve/preserve muscle mass and function with ageing and/or with diseases associated with sarcopenia in humans; however, the study by Kargl et al .…”
supporting
confidence: 61%
See 1 more Smart Citation
“…; Hafen et al . ). Much more research is needed to determine whether heat therapy would improve/preserve muscle mass and function with ageing and/or with diseases associated with sarcopenia in humans; however, the study by Kargl et al .…”
supporting
confidence: 61%
“…Moreover, recent studies have reported beneficial effects of heat therapy on skeletal muscle function. Specifically, heat therapy attenuates reductions in muscle strength and accelerates muscle regeneration and recovery following muscle-damaging exercise or injury (McGorm et al 2018) and attenuates muscle atrophy associated with limb immobilization (McGorm et al 2018;Hafen et al 2019). Much more research is needed to determine whether heat therapy would improve/preserve muscle mass and function with ageing and/or with diseases associated with sarcopenia in humans; however, the study by Kargl et al (2019), when combined with the studies of heat therapy presented here, provides compelling support for this hypothesis, and that these beneficial effects may occur via the EC secretome.…”
Section: Journal Clubmentioning
confidence: 99%
“…The potential for heat-based interventions to be an integrative part of a rehabilitation strategy has, therefore, gathered considerable enthusiasm lately. This surge in interest is in-part due to recent studies in humans demonstrating improved muscle contractile function (Racinais et al, 2017b) or attenuated loss of muscle mass during immobilization (Hafen et al, 2019) following short-term heat exposure. Specifically, Racinais et al (2017b) showed that 11 days of passive whole body heat exposure (60 min @ 48-50 • C, 50% RH) resulted in an increased peak twitch amplitude, improved maximal voluntary torque, as well as the relative torque/electromyographic relationship.…”
Section: Muscle Adaptations To Heat Therapy To Minimize Muscle Atrophmentioning
confidence: 99%
“…Specifically, Racinais et al (2017b) showed that 11 days of passive whole body heat exposure (60 min @ 48-50 • C, 50% RH) resulted in an increased peak twitch amplitude, improved maximal voluntary torque, as well as the relative torque/electromyographic relationship. Additionally, more recent data by Hafen et al (2019) showed that the decline in muscle mass following 10 days of lower limb immobilization was in-part attenuated when 120 min of localized heating of the vastus lateralis was administered daily. The preserved muscle mass following heat treatment coincided with the protein abundance of the transcriptional co-activator PGC-1α, HSP 70, and HSP 90, as well as minimized loss of mitochondrial respiratory chain protein content and mitochondrial respiratory function (Hafen et al, 2019).…”
Section: Muscle Adaptations To Heat Therapy To Minimize Muscle Atrophmentioning
confidence: 99%
See 1 more Smart Citation